FROM GLOBAL PERCEPTION TO LOCAL PATRONAGE: THE MEDIATING ROLE OF BRAND AUTHENTICITY IN INDONESIAN RESTAURANTS - JN, M Raihan; Nasution, Thorique Akbar Maulana; Nasution, Muhammad Dharma Tuah Putra (Proceeding International Conference of Science Technology and Social Humanities, 2022)
This study explores the dynamic relationships between perceived brand globalness, brand authenticity, and brand patronage within the Indonesian restaurant industry. The primary objectives are to elucidate how perceived globalness influences brand authenticity, evaluate the impact of brand authenticity on patronage, and investigate the mediating role of brand authenticity in the relationship between perceived brand globalness and brand patronage. Employing a quantitative approach, the study will gather data through surveys conducted with Indonesian consumers who frequent quick service restaurants (QSRs). The survey will measure perceptions of brand globalness, authenticity, and patronage. Data analysis will be performed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypotheses and examine the relationships among constructs. The study hypothesizes that perceived brand globalness will positively influence brand authenticity, suggesting that enhanced global recognition is expected to boost brand patronage through associations with higher quality and prestige. Additionally, it is anticipated that brand authenticity will positively impact patronage by fostering stronger emotional connections with consumers. Furthermore, brand authenticity is expected to mediate the effect of perceived brand globalness on brand patronage, indicating that the impact of globalness on patronage is significantly mediated by perceived authenticity. The findings are anticipated to provide valuable insights for restaurant managers, guiding strategies to enhance brand positioning and consumer engagement. This research highlights the critical importance of aligning global and authentic brand attributes to enhance consumer loyalty in the restaurant sector.